Philosophy of Humour : New Perspectives - Bachmetjevas, Viktoras,; O'Shiel, Daniel, (Value Inquiry Book Series ;, 2023)
This volume aims to reignite interest in a sorely neglected field within philosophy: the philosophy of humour. Indeed, although humour, jokes and laughter make up a quintessentially human domain of extreme universal importance, it has not received the sustained and involved attention and investigation that it merits. This volume draws on theories both distant and more nearby in order to contemporize the discussion into the 21st century, with each of the ten contributions demonstrating just how many perspectives and conversations are to be had, both on theoretical and concrete levels, now and going forward.